Uslub Ta’lim Maharah al-Kalam Bi Asas al-Dzaka’at al-Muta’addah Fi al-Marhalah al-Ibtidaiyyah - Rasyidi, Abdul Wahab; Febriani, Suci Ramadhanti (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This research aims to describe the technique of teaching speaking skills in Al Kautsar Elementary School, which was packaged using multiple classroom management based on multiple intelligences and factors that influence the success of the speech skill teaching method in each different class. The researcher used the descriptive qualitative approach, observational and interview data collection, documentation and data analysis with the data triangle. The results show that Al-Kautsar Elementary School organized the education program well, which is characterized by applying the teaching method of speaking skill on the basis of multiple intelligences by producing a variety of different speaking skill teaching method according to students' intelligence means guessing the word, singing, training and physical movement. Thematic and humanistic education curricula were implemented in an integrated way to encourage the achievement of good educational results and the production of speech skill. Then the factors that affect the success of speech skill education in primary school include Al Kautsar consisting of a strong funding factor, environment, reliable human resource management and organized school management. This research suggests the need to reformulate the method of teaching speech skills to administer the teaching of Arabic language in the global age to establish it at the institute.